Decisive insight on communal and moral assessment of Islamic banking: is it identical to social and ethical banking? - Hassan, Rusni; Yusoff, Adnan (Serials Publications, 2010)
There are three modes of banking system available in the world - ethical banking, social banking and Islamic banking. The emergence of Islamic banks is to introduce the ethical aspects that seem to be long forgotten into the current global financial system. The paper will compare and contrast the three concepts of banking - Islamic banking, ethical banking and social banking. Such comparative analysis will be made based on specific aspects of banking and overview of all three banking systems. Given the different natures of these banking concepts, it is indeed interesting to see where these differences converge and how their co-existence complements their respective growth. More importantly, this paper aims to explore the potential of the Islamic banking industry to incorporate these three noble concepts into one "just" banking system.